The Role of Teachers in Forming the Citizenship Character of Elementary School Students - Br Tarigan, Grace Gita Terulin (International Journal of Students Education, 2024)
The role of Citizenship Education teachers in forming the disciplined character of students in schools is a primary responsibility of teachers. This role relates to the development of three aspects: politics, law, and morality. The method used is a literature review of various writings, both journals and books, related to the implementation of character in the role of Civic Education. From these three aspects, it is expected to shape students' knowledge to have a disciplined character in school, such as the legal aspect as an implementation of school rules or regulations. Civic skills are competencies developed from civic knowledge, intended so that the learning obtained becomes meaningful in facing the challenges of being a disciplined student at school. The results of the study showed that the PKn learning process was carried out using a guided inquiry learning model and in fostering students' curiosity character has gone well. Teachers have made many efforts to foster students' curiosity character such as communicating with students, providing motivation, provoking students' curiosity by giving students the opportunity to ask questions or providing questions that can be answered by students. Civic dispositions are the most substantive and essential aspects of the Citizenship Education subject and serve as the estuary of the development of the two previous competencies.